Review of psychoeducation programs to prevent substance use and addiction - Yoldaş, Ceren; Demircioğlu, Haktan (Journal of Dependence, 2020)
The purpose of this study is to examine the development of training programs for the prevention of substance abuse and addiction in Turkey and other countries.As data source of the research, sample programs which is developed to prevent substance use and addiction such as Yeşilay, European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), Blueprints Programs, Substance Abuse and Mental Health Services Administration (SAMHSA) ve Reducing Alcohol Related Harm (RARHA) were used.As a result of the screening, 439 examples of national and international practices or programs for prevention, treatment and legal sanctions have been reached, and 5 from Turkey, including 19 from other countries a total of 24 prevention programs were included in the study so as to represent different groups and contents.There are extensive studies in the literature about substance use and addiction, and it is emphasized that the age of substance use is decreases worldwide as well as becoming widespread rapidly. Therefore, effective protective and preventive intervention services are needed to reduce the risk of substance abuse and addiction in individuals.